Role of Sikasep Applications in Reducing â€œHunianâ€ Backlogs - Mediaty, Mediaty; Gaol, Dody Kurnia L.; Negara, Bella Amanda (Faculty of Economics and Business, Hasanuddin University, 2022)
Utilization of information technology is not only used in business sector organizations, but also in the public sector. Utilization of technology in the form of information systems can provide efficiency in terms of facilitating human work to be faster and more accurate. The Ministry of PUPR through BLU PPDPP publishes the Sikasep application (Housing Subsidized Mortgage Information System). This Sikasep application is one form of innovation in the public service system that prioritizes accessibility, as well as being effective and time efficient. The purpose of this study is to analyze the role of the Sikasep application in reducing the housing backlog. The method used in this study is a literature review obtained from books, journals, and articles. Realization until 2021, the Sikasep application has distributed subsidized mortgages to 2,420,105 units of users. This shows that the Sikasep application has an important role in distributing subsidized mortgages for MBR.